2009
DOI: 10.1093/ejechocard/jen258
|View full text |Cite
|
Sign up to set email alerts
|

Using mitral 'annulus reversus' to diagnose constrictive pericarditis

Abstract: Practical applications of tissue Doppler imaging for evaluation of possible constrictive pericarditis include reversal of the relationship between lateral and medial e' velocities (i.e. 'annulus reversus').

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 9 publications
3
44
0
5
Order By: Relevance
“…However, there has been 1 report regarding a reversed relationship between lateral mitral E= (LE=) and septal annular E= (SE=) in 14 patients with CP (6). Because the adhesion of the pericardium and myocardium of the lateral wall of both ventricles could restrict both mitral and tricuspid lateral annular motion, these velocities might be smaller than SE=, and the thickness of left-and right-side pericardium would have an influence on LE= and right lateral tricuspid annulus early diastolic velocity (RE=), respectively.…”
Section: See Page 576mentioning
confidence: 99%
“…However, there has been 1 report regarding a reversed relationship between lateral mitral E= (LE=) and septal annular E= (SE=) in 14 patients with CP (6). Because the adhesion of the pericardium and myocardium of the lateral wall of both ventricles could restrict both mitral and tricuspid lateral annular motion, these velocities might be smaller than SE=, and the thickness of left-and right-side pericardium would have an influence on LE= and right lateral tricuspid annulus early diastolic velocity (RE=), respectively.…”
Section: See Page 576mentioning
confidence: 99%
“…[4][5][6] Pericardial to myocardial tethering along the left ventricular (LV) and right ventricular (RV) free wall in CP results in isolated reduction in the magnitude of longitudinal deformation of the LV and RV free walls with preserved deformation of the interventricular septal wall. 7,8 In contrast, pathological processes often involve the heart nonselectively resulting in global reduction of deformation in RCM. Previous studies have shown reduction of Dopplerderived annular velocities of the LV and RV free walls attributable to perimyocardial tethering with reversal of this phenomena after pericardiectomy.…”
mentioning
confidence: 99%
“…This phenomenon has been described as ‘annulus reversus’––normally lateral annular velocity is higher than medial annular velocity 1. The high tissue Doppler velocities distinguish constriction from myocardial disease in which tissue Doppler velocities are reduced.…”
Section: Answer:dmentioning
confidence: 99%